Denture labels: Various types and their abilities to resist different assaults - Phulari, Rashmi G. S. (J Forensic Dent Sci, 2017)
INTRODUCTION: The use of denture labels for the purpose of identification has been well documented. A number of labels for marking the denture are documented till date demonstrating the ease of fabrication and its potential value in identification. Therefore, it becomes essential that these denture labels fulfill the requisites of an ideal denture label and thus should be able to sustain the various assaults to which they might be subjected simulating a crime scene. AIM: The aim of this study was to determine the ability of various denture labels to withstand different types of assaults thereby evaluating the performance of routinely used denture labels. MATERIALS AND METHODS: Four polymethylmethacrylate blocks were fabricated where the inclusion labels were incorporated on one side, and the surface labels were marked on the other side. Each of the blocks was then placed in different containers to be subjected to different assaults such as acid, alkali, water, and heat of increasing temperature. RESULTS: Inclusion labels performed better as compared to surface marking labels. Among the inclusion labels, the metallic labels performed the best. CONCLUSION: The metallic inclusion labels were able to withstand most assaults than any other inclusion labels or surface marking labels. Due to easy availability, cost-effectiveness, ease of incorporation and inertness, metallic labels are best suited as denture labels for personal identification.